PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SD KELAS V MELALUI PEMBELAJARAN DENGAN STRATEGI REACT - elfi - rahmadhani (EduMa: Mathematics education learning and teaching, 2017)
This article was written aimed to determine (1) mathematical communication skills of students who use the REACT strategy better than students using the conventional learning model, (2) mathematical communication skills of students who have prior knowledge of high, medium and low with using REACT strategy better than the students who used conventional learning models, and (3) the interaction between early learning approach with the ability of students to affect an improved mathematical communication skills of students. Samples were fifth grade elementary school students 03 and 04 Solok City academic years 2012/2013 as many as 56 people. Research data on study result of the students were collected through initial skills test, pretest and posttest. To see the improvement, the analysis used the gain. Based on the results of this study concluded that an increased mathematical communication skills of students using REACT strategy is better than using the conventional learning, and there is no interaction between early learning approach with the ability of students to affect an improved mathematical communication skills of students.                                                                                              Keyword: mathematical communication skills, REACT strategy